Zambon, Francesco (2021), Il fiore inverso. I poeti del trobar clus. Milano: Luni Editrice. - Pablo Acosta García (Revista de Poética Medieval, 2023)
Reseña de: Zambon, Francesco (2021), Il fiore inverso. I poeti del trobar clus. Milano: Luni Editrice.